41 Antidiabetic activity of tea polysaccharides in mice with alloxan-induced diabetes. (19th December 2016) - Liu, Yang; Li, Shuai; Cheng, Yingkun; Li, Chenliang; Wang, Di; Yan, Guodong
Abstract : Objectives: Tea has been viewed as a health drink since ancient times in China. Tea polysaccharides (TPS) extracted from tea possess antidiabetic and hypolipidemic activity. After cancer and cardiovascular diseases, diabetes is the third most common cause of death. As existing treatment is inadequate, research for better drugs should be carried out. The present study aimed to investigate the potential antidiabetic and hypolipidemic activity of tea polysaccharides in mice with alloxan-induced diabetes. Methods: Diabetic mice were divided into five groups which were orally treated with 125 mg/kg metformin and TPS at doses of 200, 400 and 800 mg/kg for 21 days. After 3 weeks of treatment, mice were sacrificed and blood was collected. Levels of blood glucose and lipids were measured using an enzyme-linked immunosorbent assay. Results: After 3-week treatment, similarly to metformin, TPS significantly decreased levels of blood glucose and increased levels of serum insulin. Treatment with metformin and TPS normalized levels of total triglycerides (TG) and total cholesterol (TC), and restored the balance between low-density lipoprotein cholesterol (LDL-C) and high density lipoprotein cholesterol (HDL-C). Conclusions: The results of the present study indicate that TPS may be a potential pharmaceutical agent for the treatment of diabetes as it normalized blood glucose and lipid levels in mice with alloxan-induced diabetes.